Understanding Work Motivation among Urban Park Management Personnel: A Case Study of Sukabumi City - Mohammad Sahid; Ely Sufianti; Muhamad Nur Afandi; Teni Listiani (Journal of Governance and Accountability Studies, 2026)
Purpose: This study examines the level and determinants of work motivation among urban park management personnel at the Sukabumi City Public Works and Public Housing Agency using Herzberg’s Two-Factor Theory and explores the presence of a mid-career plateau. Methodology: A quantitative descriptive approach was employed using a census of 49 participants. Data were collected through structured questionnaires on motivator and hygiene factors, complemented by semi-structured interviews for data triangulation. Quantitative data were analyzed descriptively, and qualitative data provided contextual interpretation. Results: Findings show that work motivation is generally good, with hygiene factors (mean = 3.31) slightly exceeding motivator factors (mean = 3.19). Working relationships were rated the highest, whereas working conditions and salary were rated the lowest. A mid-career plateau was observed among employees with 6–10 years of service, influenced by limited welfare, constrained career opportunities and inadequate work facilities. Conclusions: Despite overall positive motivation, structural issues related to compensation, career development, and the work environment continue to hinder sustained motivation. Addressing these challenges requires integrated interventions across short-, medium-, and long-term strategies. Limitations: This study was limited by its cross-sectional design, single institutional context, and exclusion of broader attitudinal variables. Contributions: This study provides empirical insights into work motivation among operational-level urban park workers and offers practical recommendations for local governments to improve public service workforce management.